Evaluation of serum and gingival crevicular fluid levels of Vitamin D binding protein in subjects with clinically healthy periodontium and chronic periodontitis: A clinico bio-chemical study - Yashaswini Chakravarthy; Ashank Mishra; Preeti Krishnan; Krishnajaneya Reddy Pathakota; V Vijaya; Shanthi Naidu Kamatham (Wolters Kluwer Medknow Publications, 2022)
Background: Advances in oral and periodontal disease diagnostic research are moving towards methods wherein periodontal risk can be identified and quantified by objective measures such as bio-markers. Given the roles of vitamin D binding protein (DBP) in modulating the immune response and in the transport of vitamin D, it is hypothesised that quantitative changes of vitamin DBP are associated with periodontal disease. Aim: The aim of the current study is to measure DBP levels in serum and gingival crevicular fluid (GCF) of patients with generalised chronic periodontitis, in comparison to healthy controls. Materials and Methods: The present cross-sectional clinico-bio-chemical study includes 30 systemically healthy subjects with 15 periodontally healthy and 15 chronic periodontitis subjects who were recruited from the out-patient Department of Periodontics. GCF and blood samples were collected from all the patients. DBP estimation was performed in both the samples using a commercially available ELISA kit. Results: Serum and GCF DBP levels in chronic periodontitis subjects were significantly higher when compared to the periodontally healthy group. There were no significant correlations found among serum and GCF DBP levels with gender and increasing age in both the groups. An increase in disease severity measured by the increase in probing pocket depth and clinical attachment loss did not show correlation with the GCF and serum DBP levels in the chronic periodontitis group. Conclusion: Based on the findings of the present study, increased serum and GCF DBP levels in chronic periodontitis seem to be a probable marker for identifying ongoing periodontal destruction.